Effects of thermal and electrical stress on DH4T-based organic thin-film-transistors with PMMA gate dielectrics. Issue 9 (August 2015) - Wrachien, N.; Lago, N.; Rizzo, A.; D'Alpaos, R.; Stefani, A.; Turatti, G.; Muccini, M.; Meneghesso, G.; Cester, A.
Abstract: We performed thermal and constant voltage stress on oligothiophene-based p-type organic thin-film-transistors. The devices subjected to thermal stress without bias showed limited variations. The bias stress performed at 20 °C induced monotonic charge trapping, and mobility degradation. The devices subjected to simultaneous thermal and bias stress featured much larger variations on both the threshold voltage and the mobility, indicating that the temperature is unable (at least within the analyzed range) to induce strong degradation, but it can strongly accelerate the bias stress effects.